Posted by **george** on Thursday, January 7, 2010 at 2:43pm.

Simplify 3(x - 4) + 8(x + 2).

A)11x - 4

B)11x + 4

C)11x - 2

## Answer this Question

## Related Questions

- math - I solved this problem 12x-6=11x -6+6=0 11x+6 12x=11x+6 12x-11x=x 11x-11x=...
- Algebra 1b! - 1. Find the excluded value of x for the polynomomial expression ...
- math polynomials - Simplify 4q^2-5q-1+8q^2+8q-9 A. -4q^2+3q+8 B. 12q^2+3q-10 C...
- Math - Can anyone help work these problumns out step by step? 11x-37=x+23 10p-26...
- Algebra - Add the following (-8^2-2x+4)+(x^2-9x+7) A)9x^2-7x+11 B)-8x^2+11x+11 C...
- math - simplify and state any restrictions: 1. x+3/x^2+11x+24 - 2x+10/x^2+11x+30...
- Math - Simplify 6x + 6 + 5x - 8. A)11x - 2 B)11x + 2 C)9x
- Math - Simplify 6x + 6 + 5x - 8. A)11x - 2 B)11x + 2 c)9x
- algebra - Can anyone tell me if I got this problem right 12x-6=11x 12x-6+6=11x+6...
- math - The equation that has the roots 1, 2, 3 is: (a) x3 + 6x2 – 11x + 6 (b) x3...

More Related Questions